MULTIKULTURALISME DALAM SEJARAH ISLAM - Harahap, Jahrona; Albina, Meyniar (Pengelola Jurnal Politeknik Negeri Ketapang, 2025)
This research aims to find out how multiculturalism was in Islamic history, both during the time of the Prophet, Muhammad Saw, the Abbasid period, and the Umayyah. The research method used is library research or library research. Library research is research in which data collection is carried out by collecting data from various literature. The literature studied is not limited to books but can also include documentation materials, magazines, journals and newspapers. The emphasis of library research is to find various theories, laws, postulates, principles, opinions, ideas and so on that can be used to analyze and solve the problems studied. The results of this research are: Multiculturalism began to develop beyond the limits of diversity in native Arab society. This cultural diversity occurred because of the relationship between cultures outside Islam and outside Arab culture. During the reign of the Abbasid dynasty, Islamic culture met Arab, Persian, Roman and Indian culture.